The Utilization of Taro leaf Silage (Alocasiamacrorhiza) with Marine Yeast Inoculant in Feed of Tambaqui (Colossoma macropomum) - Rahmad Siddiq; Adelina '; Hamdan Alawi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The purpose of this study was to determine the effect of silage use sente leaves on feed efficiency and growth of freshwater pomfret (Colossoma macropomum). The method used in the study is an experimental method by using a completely randomized design (CRD) of the factors with 5 level treatment and 3 replications., With treatment P0 (100% TK: 0% DS), P1 (80% TK: 20% DS ), P2 (60% TK: 40% DS), P3 (40% TK: 60% DS), P4 (20% TK: 80 DS) and P5 (0% TK: 100% DS). The results showed the use of leaf sente 100% was significantly lower than soybean meal, meaning can not fully replace soybean meal. But yielded significant results on the growth and retention of fish protein with the addition of 20 and 40% soybean meal in feed freshwater pomfret (Colossoma macropomum). The best treatment is obtained on the use of silage flour sente leaves as much as 40% with an average daily growth rate of 3.98% and feed efficiency of 45.63%.Key word : Taro leaf, silage, Tambaqui